Determination of background, signal‐to‐noise, and dynamic range of a flow cytometer: A novel practical method for instrument characterization and standardization. Issue 11 (27th September 2017) - Giesecke, Claudia; Feher, Kristen; von Volkmann, Konrad; Kirsch, Jenny; Radbruch, Andreas; Kaiser, Toralf
Abstract: A well‐defined scale calibration in flow cytometry can improve many aspects of data acquisition such as cytometer setup, instrument comparison and sample comparison. The theory for scale calibration was proposed by Steen over two decades ago, but it has never been put into regular use due to the lack of a widely available precision light source. The introduction of such a light source, the quantiFlash TM, gave this possibility. Here, we describe how this light source can be used to characterize a cytometer's PMT performance. We, therefore, characterized the instrument's response over the entire PMT voltage range. As a consequence, we propose a practical method to characterize a cytometer's signal‐to‐noise ratio (SNR) and dynamic range (DNR). This allows the selection of a voltage/gain corresponding to a PMT's maximum efficiency and hence the lowest electronic noise, which can help with experiment design. We further introduced a decibel (dB) scale for the presentation of SNR and DNR values. SNR and DNR are stand‐alone values that allow the direct comparison of different instruments. Finally, with this method, it becomes clear that increased SNR comes at the expense of DNR and thus the limiting factor of modern cytometers is the DNR. © 2017 International Society for Advancement of Cytometry